36Cl contribution for dating groundwaters from the Guarani Aquifer System - Bonotto, Daniel Marcos [UNESP]; Fifield, Leslie Keith; Eslamian, Saeid (My University, 2020)
The field of groundwater age dating nowadays considers a groundwater sample not as water that recharged the flow regime at a point in the past, but as a mixture of waters that have resided in the subsurface for varying lengths of time. This recognition resolves longstanding inconsistencies encountered in age dating and suggests new ways to carry out age dating studies. Groundwater age dating takes advantage of the known decay rates of radioactive isotopes, the timing of the introduction into the atmosphere of isotopes from nuclear testing or reactors, or the history of the release of manufactured gases to estimate the age of a groundwater sample. 36Cl has properties which make it suitable for the study of confined groundwaters. Its long half-life (301 ka) and the fact that chloride is not removed from solution by mineral interaction or secondary mineral formation would, in principle, permit the estimation of very long groundwater residence times. This chapter reports the use of the 36Cl method for estimating the groundwater residence time in the northern part of the Guarani Aquifer System (GAS) in Brazil. It underlies 1.2M km2 in the Paraná sedimentary basin of South America and is an important source of water for industry, agriculture and domestic supplies. The isotopic database was set after collecting and analyzing rainfall and groundwater samples coming from São Paulo and Mato Grosso do Sul states, helping to understand the dynamics of this groundwater system and its sustainability. The ages varied between 43.8 ka and 2.0 Ma that exceed the range of 30-40 ka from the conventional 14C dating, thus, expanding the results obtained from previous work in the region, including other radio-isotope analyses.
Keywords: 36Cl measurements; AMS-accelerator mass spectrometry; Dating; GASGuarani aquifer system; Groundwater; Residence time